2012
DOI: 10.1093/aje/kws297
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Investigating Associations Between Healthy Diet and Fasting Glucose and Insulin Levels and Modification by Loci Associated With Glucose Homeostasis in Data From 15 Cohorts

Abstract: Whether loci that influence fasting glucose (FG) and fasting insulin (FI) levels, as identified by genome-wide association studies, modify associations of diet with FG or FI is unknown. We utilized data from 15 U.S. and European cohort studies comprising 51,289 persons without diabetes to test whether genotype and diet interact to influence FG or FI concentration. We constructed a diet score using study-specific quartile rankings for intakes of whole grains, fish, fruits, vegetables, and nuts/seeds (favorable)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 44 publications
6
55
1
5
Order By: Relevance
“…A diet score that reflected healthy eating habits was calculated as previously described (32). Briefly, the daily intake frequency was calculated for 8 food and beverage groups.…”
Section: Dietary Assessmentsmentioning
confidence: 99%
“…A diet score that reflected healthy eating habits was calculated as previously described (32). Briefly, the daily intake frequency was calculated for 8 food and beverage groups.…”
Section: Dietary Assessmentsmentioning
confidence: 99%
“…19) for processed meat, after multivariate analyses [15]. A meta-analysis showed no interactions between dietary patterns and diabetes risk genetic loci on glucose and insulin levels [16], suggesting no individual genetic differences in susceptibility to the effect of diet on the risk of T2DM. However the association between red meat and diabetes may be confounded by other imperfectly measured or unmeasured lifestyle attributes.…”
Section: Meta-analyses Of Red and Processed Meat Intakementioning
confidence: 99%
“…Nettleton JA et al 19 recently reported a meta-analysis investigating associations between healthy diet, fasting glucose, insulin levels, and genetic loci associated with glucose homeostasis. They utilized data from 15 USA and European cohort studies comprising 51,289 persons without diabetes to test whether genotype and diet interact to influence glucose or insulin concentration.…”
Section: Ideally Balanced Healthy Diet and Dietary Habitsmentioning
confidence: 99%